Studies on mass energy-absorption coefficients and effective atomic energy-absorption cross sections for carbohydrates. (April 2015) - Ladhaf, Bibifatima M.; Pawar, Pravina P.
Abstract: We measured here the mass attenuation coefficients ( μ / ρ ) of carbohydrates, Esculine (C15 H16 O9 ), Sucrose (C12 H22 O11 ), Sorbitol (C6 H14 O6 ), d -Galactose (C6 H12 O6 ), Inositol (C6 H12 O6 ), d -Xylose (C5 H10 O5 ) covering the energy range from 122 keV up to 1330 keV photon energies by using gamma ray transmission method in a narrow beam good geometry set-up. The gamma-rays were detected using NaI(Tl) scintillation detection system with a resolution of 8.2% at 662 keV. The attenuation coefficient data were then used to obtain the total attenuation cross-section ( σ tot ), molar extinction coefficients ( ε ), mass-energy absorption coefficients ( μ en / ρ ) and effective (average) atomic energy-absorption cross section ( σ a, en) of the compounds. These values are found to be in good agreement with the theoretical values calculated based on XCOM data. Highlights: Compute the values of mass attenuation coefficients ( μ / ρ ) of some carbohydrates. The values of ( μ en / ρ ) i.e. mass energy-absorption coefficient are calculated. Effective atomic energy-absorption cross sections ( σ a, en) . Comparison of all ( μ / ρ ), ( μ en / ρ ), ( σ a, en ) values with XCOM program. The measured data for carbohydrates are useful in radiation dosimetry and other fields.